Implementation of TQM and the Impact on Performance of an Organization a Case Study at Kayaba (M) Sdn Bhd - Rajagopal, Anbalagan (1997)
The purpose of this study is to identify and determine the principles and the steps of implementation of TQM program at Kayaba (M) Sdn. Bhd. It is also to determine and evaluate the impact of TQM practices on the performance of the company and analyze the effectiveness of empowerment given by Kayaba (M) Sdn. Bhd. Management to their employees. The findings of the study showed that TQM program improved the overall company's performance such as improved operating procedure, better employee relations , greater customer satisfaction and improvement of the company's financial performance . The study also prove of that Kayaba (M) Sdn. Bhd. is committed to delegating empowerment to their employees to a greater extend inline with TQM concept. The findings of this study has shown that overall commitment and continuous effort in promoting TQM concept enables employee to be a leading manufacturer and supplier of shock absorber and power steering pump in Malaysia.